2015
DOI: 10.2522/ptj.20140137
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vibration Therapy on Immobilization-Induced Hypersensitivity in Rats

Abstract: The data suggest that initiation of vibration therapy in the early phase of immobilization may inhibit the development of immobilization-induced hypersensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 53 publications
0
25
0
Order By: Relevance
“…In experimental studies using animal, cast immobilization of limbs causes hyperalgesia, which is a decline of the threshold of mechanical and thermal mechanical stimuli [1,2], and limb immobilization for long durations may induce chronic pain associated with central sensitization [3].…”
Section: Introductionmentioning
confidence: 99%
“…In experimental studies using animal, cast immobilization of limbs causes hyperalgesia, which is a decline of the threshold of mechanical and thermal mechanical stimuli [1,2], and limb immobilization for long durations may induce chronic pain associated with central sensitization [3].…”
Section: Introductionmentioning
confidence: 99%
“…Further, Hamaue et al claimed that only a 4-week immobilization resulted in hypersensitivity [ 18 ]. In this study, however, we did not observe any changes in the sensory threshold even without vibration ( Fig 3D ) [ 21 ]. The casting and non-weight-bearing conditions did not cause hypersensitivity in the acute stage after cast removal, even after 6 weeks of immobilization, probably due to the measurement of the sensory threshold.…”
Section: Discussionmentioning
confidence: 63%
“…Previous studies have showed that immobilization in rodents causes hypersensitivity [ 17 20 ] and that continuous vibration or treadmill training partially recovers the hypersensitivity [ 21 23 ]. Further, Hamaue et al claimed that only a 4-week immobilization resulted in hypersensitivity [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations